Organizational Justice as an Outcome of Diversity Management for Female Employees: Evidence From U.S. Federal Agencies - Sungchan KIM; Soyoung PARK (Transylvanian Review of Administrative Sciences, 2016)
Diversity management has been implemented vigorously in organizations with workforce diversity practices. One of the possible outcomes of diversity management is increased fairness in the organization. However, women perceive organizations as still being unfair, even though diverse managerial practices have been adopted to address equity related problems. In this article, we examine how female employees in federal agencies view diversity management and whether they believe that diversity management can lead to organizational justice. By using the 2013 Federal Employee Viewpoint Survey (FEVS) data, we found that diversity management leads to a higher level of organizational justice for female employees. However, white female employees have a higher agreement on the effi cacy of diversity management in producing procedural and interactional justice than do non-white female employees. Also, female employees in the regulatory or redistributive agency category perceive less that diversity management leads to organizational justice than those in other agencies. We therefore conclude that diversity management is an effective tool to achieve organizational justice for particular groups.